SUNTINGAN DOKUMEN BERBASIS WEB - ANISYA, ANISYA; WARMAN, INDRA; TRISE PUTRA, DEDE WIRA (Jurnal EDik Informatika, 2021)
Web-based document editing is a system for making scientific papers without having to adjust the format of writing scientific papers. Where in this system has provided a framework for entering journal contents. Journal article creation must follow the format already in place in the organization, such as font size, edge size, and so on. Often in writing journals, writers experience difficulties or constraints in the format of writing, so they often experience errors in writing journal articles. For this reason, it is necessary to have a standard web journal writing program, which provides a framework for the format of journal writing. The process carried out in designing this application is  by looking  at  the guidelines  for  journal  manuscript  writing, with  these guidelines the writer can know how the journal format will be translated into a program script. The purpose of this research is to design a standard web program for editing documents in journals and to assist journal authors / journal authors in making scientific papers online. In this research, the writer made a document editing system for scientific journal writing format using PHP and MySQL in the application system. Where in the system designed the author only includes the entries of each input in the journal framework. In this system all the input that is filled in is stored in a database with different tables. And when the author sees the contents of the journal, the display on the journal contents automatically matches the journal template.